PERENCANAAN SISTEM PENYALUR PETIR ELEKTROSTATIS DENGAN METODE SANGKAR FARADAY PADA GEDUNG KEUANGAN NEGARA KUPANG - Agusthinus S. Sampeallo; Evtaleny R. Mauboy; Yeremias M. Moron (Universitas Nusa Cendana, 2020)
Gedung Keuangan Negara (GKN) of Kupang is the office for the affairs of the state finance and assets. The Franklin type lightning in the State Finance Building is not functioned properly and the value of resistance is quite large plus the number of thunder days in Kupang city reaches 80 thunder days and 128,504 lightning strikes in 2019 according to data from the Kampung Baru Kupang Geophysical Station. The results of primary and secondary data collection according to Indonesian National standards (SNI 03-7015-2004) Gedung Keuangan Negara must be protected from lightning induction because the value of the annual average frequency of direct lightning strikes (Nd) > the allowed local annual lightning strike frequency (Nc). Electrostatic protection is selected for the electrostatic type with a Flash Vectron FV6 type with a radius of 50 to 150 combined with a Faraday cage of 8 finials and funneled through a Bare Cooper conductor 50 mm^2 to grounding system planted in the ground with a rod type electrode diameter of 12 millimeters in length. The electrodes planted varied, namely 0.5 meters, 1 meter and 1.5 meters. The value of grounding resistance R<5 Ω is in accordance with the PUIL 2011 standard. The value of earthing resistance R_average L_(0,5 m)=171,6 Ω, L_(1.0 m)=128,6 Ω and L_(1,5 m)=73,4 Ω. To fulfill the requirements according to the PUIL standard, the number of rods in L_(0,5 m) must be added with the value of R_paralel = 3,7065 Ω for 100 electrode rods, for L_(1 m) with a value of R_paralel= 3,9682 Ω for 70 electrode rods, and for L_(1,5 m)= 3,1708 Ω for 50 electrode rods.